1992
DOI: 10.1021/ac00038a021
|View full text |Cite
|
Sign up to set email alerts
|

Conformational effects in the reversed-phase chromatographic behavior of recombinant human growth hormone (rhGH) and N-methionyl recombinant human growth hormone (Met-hGH)

Abstract: This paper examines the retention behavior of recombinant DNA-derived human growth hormone (rhGH) in reversed-phase chromatography and its separation from the closely related N-methionyl variant (Met-hGH). It is first shown that retention for rhGH decreases with increasing column temperature when 1-propanol (1-PrOH) is used as organic modifier. On the other hand, retention increases with temperature when acetonitrile (CH3CN) is employed. The differences in behavior for the two organic modifiers could be relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 25 publications
2
38
0
Order By: Relevance
“…The observed maximum at 338 nm for hGH in solution might be the result of the polarity which arises from an H-bond of the tryptophan with an aspartic acid residue. 29 As can be seen from both the λ m shifts and the quenching constants, relatively large changes are observed for adsorption onto the OTS and DDS surfaces. These were also the surfaces for which hGH showed the highest affinity.…”
Section: Conformational Changesmentioning
confidence: 94%
“…The observed maximum at 338 nm for hGH in solution might be the result of the polarity which arises from an H-bond of the tryptophan with an aspartic acid residue. 29 As can be seen from both the λ m shifts and the quenching constants, relatively large changes are observed for adsorption onto the OTS and DDS surfaces. These were also the surfaces for which hGH showed the highest affinity.…”
Section: Conformational Changesmentioning
confidence: 94%
“…The concentration and intensity are both a function of the distance from the interface into the cell. The observed fluorescence signal, S, can therefore be written as [3] in which f is an instrumental factor characterized by the efficiency in which the fluorescence is detected.…”
Section: Calibration Of Tirfmentioning
confidence: 99%
“…The fluorescence of TRP emanates from molecules in solution which are excited by the evanescent wave and can be derived by integration of Eq. [3]. The size of an adsorbed protein is two orders of magnitude less than the penetration depth and therefore the protein concentration profile can be considered as a quantity equal to the surface concentration, Γ p , positioned at z = 0.…”
Section: Calibration Of Tirfmentioning
confidence: 99%
“…The potential for conformational changes and yield losses induced by HIC media can further complicate process development. Protein conformational changes are known to occur when exposed to the strong hydrophobic surfaces of reversed phase chromatography (RPC) (Benedek et al, 1984;Cohen et al, 1985;Lu et al, 1986;Gooding and Regnier, 1990;Oroszlan et al, 1992;Fernandez, 1999, 2001;). Losses of enzyme activity (Kato et al, , 1986Josic et al, 1986) and low chromatographic recovery (Ichinose et al, 1985;Fausnaugh et al, 1984a,b;Kato et al, 2002) have also been reported for some HIC media, even though they are the much less hydrophobic than RPC resins.…”
Section: Introductionmentioning
confidence: 99%